Models for Mental Disorder. - Tyrer, Peter (Wiley, 2013)
Models for Mental Disorder, first published in 1987, anticipated the move towards integration of psychiatric services into multidisciplinary teams (doctor, psychologist, nurse, social worker, etc) and the need to bring together the different philosophies of mental illness. Peter Tyrer has identified four different models of mental disorder that are relevant to clinical practice: the disease, psychodynamic, cognitive-behavioural and social models. Each model is described and reviewed, with reference to case studies and illustrations, to show how it relates to mental health disorders and can.